2014
DOI: 10.1159/000362811
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gestational Age on Targeted Amniotic Cell Profiling in Experimental Neural Tube Defects

Abstract: Purpose: The proportions of select stem cells in term amniotic fluid have been shown to correlate with the type and size of experimental neural tube defects (NTDs). We sought to determine the impact of gestational age upon this form of targeted amniotic cell profiling. Methods: Sprague-Dawley fetuses with retinoic acid-induced NTDs (n = 110) underwent amniotic fluid procurement at four time points in gestation. Samples were analyzed by flow cytometry for the presence of cells concomitantly expressing Nestin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We also showed that these cells exist along with SOX-2 and nestin positive cells, GFAP positive astrocytes, and doublecortin positive neurons. Thus, the data presented here combined with previous reports [ 29 31 ] shows neural cells isolated from the AF in the setting of neural tube defects contain various populations of neuroepithelial cells.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We also showed that these cells exist along with SOX-2 and nestin positive cells, GFAP positive astrocytes, and doublecortin positive neurons. Thus, the data presented here combined with previous reports [ 29 31 ] shows neural cells isolated from the AF in the setting of neural tube defects contain various populations of neuroepithelial cells.…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, AF-derived cells have emerged as a potential supportive strategy for prenatal diagnosis of neural tube defects. In studies of AF cells in neural tube defects, the emphasis was on detection of neural cells from AF and more recently the impact of gestational age on relative proportions of select populations of AF cells [ 31 ]. In our studies, we showed the presence of unique cluster-forming population of neuroepithelial cells in the AF of MMC fetuses at stages pathologically associated with spinal cord injury assessed by immunohistochemical examination of astrogliosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the amniotic fluid may be an accessible source of (autologous) NSCs relevant to the development of new therapies for spina bifida adds another facet to the TRASCET concept. In addition, recent studies suggest that this unique population of stem cells may also have diagnostic value in the setting of congenital NTDs, besides a potential therapeutic one (17,18). Certainly, the perspective of other disease-associated amniotic stem cells being eventually described, along with roles for such cells in select clinical scenarios, is now to be expected.…”
Section: Disease-associated Amniotic Stem Cellsmentioning
confidence: 99%
“…This finding supports the notion that the inherent biological activity of afMSCs constitutes a central underlying mechanism of defect coverage triggered by TRASCET, which may simply represent an augmentation of such activity via the large number of cells delivered. In fact, recent studies suggest that afMSCs may actually be consumed in the presence of NTDs (17,18). Although the ontogeny of afMSCs and placental MSCs remain to be fully elucidated, there is evidence that they actually could be the same cell, possibly with normal traffic between the amniotic and placental compartments (54)(55)(56).…”
Section: Amniotic Mscsmentioning
confidence: 99%